PENGARUH MODIFIKASI OLAHRAGA BULUTANGKIS TERHADAP KONSENTRASI SISWA TUNARUNGU - Muhammad Akram; Arimbi Arimbi; Sarifin G (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This study aims to determine whether there is a power comparison. This study aims to determine the effect of modified badminton on the concentration of deaf students at SLB Laniang. This research is a descriptive correlational research. The data collection technique was carried out using the pre-test and post-test methods to see the value of the concentration level by involving as many as 10 samples of deaf students at SLB Laniang as research subjects. The results of this study indicate that there is an influence or change in the level of concentration related to the modification of badminton given to deaf students at SLB Laniang, this is evidenced by the T-test Significance value of 0.00 < 0.05 (significance level) which states significant. This is certainly influenced by the modification of exercise that triggers endorphins in the brain so that it stimulates the level of concentration in the sample or research subject